Leadership style and organizational performance in family owned small scale manufacturing industries in sri lanka. - Pushpanathan, A.; Mangaleswaran, T.; Lin, Z. (Faculty of Management Studies and Commerce, University of Sri Jayewardenepura, Sri Lanka., 2008)
Leadership in a family business is a far different challenge than leadership in any other kind of business. The leadership in the family business is aimed at helping business-owning families understand and implement the extra dimensions of leadership that family firm require. This study explores the leadership style and organizational performance in small scale manufacturing industries in Sri Lanka. This study utilized data from 220 small scale manufacturing industries those who are registered under the Chambers of Commerce in Sri Lanka. The relationship between three leadership styles – task-oriented, relationship-oriented, and participative – and firm performance were discussed through the moderating effect of environmental factors (Industry technology, family and non-family controlled firm and firm development stage), and mediating effect of decision making, employee turnover, and employee morale. The hypotheses were tested through matched data set. The results indicated that leadership styles were directly linked to firm performance.
Keywords: Leadership Style.; Decision making.; Employee turnover.; Employee Morale.